Delays in the Execution of Inclusive Education (IE): Preparedness of Education System in Punjab - Fauzia Khurshid; Muhammad Shahid Farooq (JCTE, 2025)
Present study explores reasons for delays in the execution of inclusive education practices in Punjab and assessed the education system's preparedness for this task. Questions of the study were: what is current position of IE in schools working in SED across Punjab? Is School Education Department of Punjab ready to accommodation of children with disabilities in mainstream schools, with reference to admission policy, physical arrangements, teacher preparation, syllabus, coordination among allied authorities? Population encompassed educational stakeholders of SED and SPED. Purposive sample was collected from the professionals working at the top management of SED, PMIU, QAED, PEC, & SpED). Qualitative data was gathered through in-depth interviews with stakeholders from various departments. Key findings include, delayed practices, lack of commitment, insufficient dedication from stakeholders, poor coordination between departments were major obstacles to implementation of IE. In addition to this, rapid transfer creates disruptive impact to sustain efforts. It is suggested that strong government support and determination, stakeholder seriousness and inter-departments coordination is required to clearly defined roles, responsibilities, and timelines without further delays.